PERFORMANCE OF SUNFLOWER IN RESPONSE TO EXOGENOUSLY APPLIED SALICYLIC ACID UNDER VARYING IRRIGATION REGIMES - M. Ahmad alias Haji A. Bukhsh; A. U. Malik; M. Ishaque; Shahwaiz H Sadiq (Journal of Animal and Plant Sciences, 2009)
A field experiment was conducted to evaluate the performance of sunflower in response of exogenously applied Salicylic Acid (SA) under varying irrigation regimes at Agronomic Research Area, University of Agriculture, Faisalabad, during spring 2007. The experiment was laid out in randomized complete block design with split-plot arrangement and replicated thrice. Net plot size was 3 m x 5 m. Irrigation regimes were kept in main plots and foliar application of SA regimes in sub plots. Irrigation regimes comprised of I1: control (Normal irrigations), I2: Irrigation missing at vegetative stage (drought stress at vegetative stage), and I3: Irrigation missing at flowering stage (drought stress at flowering), where as exogenous SA application comprised of F0: Control (no application), F1: Foliar application of 100 ppm SA at vegetative stage, F2: Foliar application of 100 ppm at flowering stage. It was observed that among various irrigation regimes, maximum number of achenes head-1 (1164.67), achene yield (2857.11 kg ha-1), biological yield (11412.00 kg ha-1), harvest index ( 25.18 % ), and achene oil (41.48 % ), was noted when crop was grown under normal irrigation regimes, where as minimum achene protein content (22.63 %) was recorded when crop was irrigated normally. The minimum values of above parameters were recorded, when crop was missed irrigation at flowering stage. Correspondingly, among different treatments of exogenous application of SA, maximum number of achenes head-1 (986.11), achene yield (2601.00 kg ha-1 ), biological yield (10822.56 kg ha-1), harvest index (25.43 % ), and achene oil (40.72 %), and minimum achene protein content (22.92 %) was recorded, when foliar application of SA (100 ppm) was done at vegetative stage. Likewise, the minimum values of above parameters were recorded, when foliar application of SA (100 ppm) was done at flowering stage. It may be concluded that maximum achene yield would be obtained when crop was irrigated normally. Drought stress both at vegetative and flowering stage badly affected the crop growth and yield components but stress at flowering stage was more damaging. Exogenous application of SA significantly ameliorated the negative effects of drought stress at both stages.
Keywords: Sunflower; Irrigation regimes; Exogenous application of Salicylic Acid; growth; yield; oil; protein contents